Analisis Dampak Program Pemberdayaan Terhadap Kesejahteraan Umat - Ferry Khusnul Mubarok (Universitas Muhammadiyah Sidoarjo, 2021)
Poverty is still a problem, especially in realizing prosperity. Many programs are carried out to alleviate poverty, one of which is the empowerment program carried out by Islamic microfinance institutions. This study aims to identify the effect of empowerment contracts on people's welfare. This study uses a quantitative approach. This study uses primary data obtained from interviews, observation, documentation. The data analysis technique used a regression approach. The results and discussion showed that the empowerment contract which included the qardhul hasan and musyarakah contracts had a significant effect on customers' income. Thus, empowerment through the qardhul hasan and musyarakah contract schemes can be developed to realize the welfare of the people.